“STRIPPED WALLETS, RIPPED HEARTS” VICTIMS OF FINANCIAL FRAUD: AN ANALYSIS BEYOND FINANCIAL FRAUD - Joomratty, Quraisha Bibi (PEOPLE: International Journal of Social Sciences, 2019)
There is a strong sense of negativity attached to victims of financial fraud. Despite the media are filled with their stories, the comprehension of the real victimisation experiences are not that evident. Victims of financial fraud are often viewed as individuals who lost only their money. Along with that they are considered as greedy and a sense of blame is thrown at them. Therefore a study beyond the financial loss was warranted. The aim of this paper is to examine the impacts of fraud victimisation other than financial impact. As the first objective, the theoretical background, including victim blaming theory, just world theory, were analysed. Secondly the emotional and psychological impacts, reporting experiences and seeking formal help were examined in relation with the responses of the victims. Based on interviews with 30 victims of fraud which consisted of victims of swindling, embezzlement, credit card fraud and Ponzi scheme, this paper establishes the profound emotional and psychological impact post victimisation. The paper also examined victim blaming, relationship breakdown, vulnerability of older people and in the worst case suicide.